Pengaruh profitabilitas, likuiditas, leverage, sales growth,dan firm size terhadap kebijakan dividen pada perusahaan sektor energi yang terdaftar di bursa efek indonesia periode 2016-2020 - Hermanto, Lisa Tesalonika; Fitriati, Ika Rosyada (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Energy sector companies include companies that sell products and services related to energy extraction, which include non-renewable energy and fossil fuels, so their income is directly affected by world energy commodity prices. There is a gap between the dividend irrelevance theory and several energy sector companies listed on the Indonesia Stock Exchange. This study aims to analyze the effect of profitability, liquidity, leverage, sales growth, and firm size on dividend policy. This research was conducted on energy sector companies listed on the Indonesia Stock Exchange (IDX) using valid annual financial statments. The sampling method uses financial reports published on the official website, namely www.idx.com with the data period from 2016 to 2020. the relationship and or influence between variables is explained by the descriptive test method. The results show that profitability, liquidity, and company size have a significant positive effect on dividend policy, while leverage and sales growth have a significant negative effect on dividend policy in energy sector companies listed on the Indonesia Stock Exchange.